On optimization of educational m anagement in the field of training for oil and gas enterprises and organizations in framework og Bologna process - Кісь, Г. Р.; Тимошенко, Д. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The article deals with the approach to educational process optimization within the framework of the Bologna Process. Attention is drawn to coaching methods and ways of “soft skills” (personality factors) implementation in order to make students to form a kind of perceptual unit (vision) of modern business processes.